PORNOGRAFI DAN PORNOAKSI DALAM PERSPEKTIF HUKUM ISLAM - Hannani Hannani (DIKTUM: Jurnal Syariah dan Hukum, 2012)
This paper describes the problem Pornography and pornographic in perspective of Islamic law. From the day the results of the study some literature gained an understanding that pornography and porno-action basically there and known since time immemorial even as old as the history of human civilization in the world. The history of pornography in the Western world mostly refer to the Renaissance, the Enlightenment and the French Revolution. In the 16th century, the roots of pornography in the Western world is considered as a balance between the field of politicians, and sexual. Some of the things a means of dissemination are: First, the internet through various websites that describe and create a narrative about the sexual activities of artists and other public figures to ordinary people with different sexual activities either normal or abnormal (homo-sexual, lesbian etc. other). Second, through television soap operas, stories about celebrities, music performances presenting Nudity. Third, tabloids and magazines that display images of half-naked to the naked full of stories from the myth to the real story about sex. Fourth, sex teaching aids such as artificial genitals (there are electronic vibration and warmth made) that can be used for deviant sex offender. Fifth, the computer programs are filled with a variety of films, stories and pornographic images. Sixth, telephone and mobile phone to be used as a means to make it easier affair, either through direct negotiations or through spoofed SMS to further facilitate the acronym of cheating. Pornography in the perspective of Islamic law are forbidden, it is clearly a normative based on several verses in Surah al-Nur verse 30, 31 'and surah al-Isra' verse 32. And some of the traditions of the Prophet, Which expressly prohibits. In addition, the provisions of the MUI Fatwas No. dated August 22, 2001. year 287 2001 clearly and unambiguously forbids pornography in all its forms.